Vaccines against mpox: MVA-BN and LC16m8 - John D. Grabenstein; Adam Hacker (Taylor & Francis Group, 2024)
Introduction Global outbreaks involving mpox clade IIb began in mid-2022. Today, clade IIb and clade I outbreaks continue. Reliable mpox vaccines can prevent serious mpox disease and death.Areas covered Globally, two vaccines hold mpox indications, regardless of mpox viral clade: MVA-BN (Bavarian Nordic) and LC16m8 (KM Biologics). This review summarizes the human and pivotal animal data establishing safety and efficacy for MVA-BN and LC16m8, including real-world evidence gathered during mpox outbreaks from 2022 through 2024.Expert opinion Some regulatory decisions for MVA-BN and LC16m8 followed pathways based on surrogate outcomes, including lethal-challenge studies in nonhuman primates, among other atypical aspects. Nonetheless, MVA-BN and LC16m8 hold unencumbered registration in multiple countries. Effectiveness of MVA-BN as primary preventive vaccination (PPV) in humans against clade IIb mpox is clear from real-world studies; effectiveness of LC16m8 against clade IIb is likely from surrogate endpoints. Effectiveness of MVA-BN and LC16m8 as PPV against more-lethal clade I is likely, based on animal-challenge studies with multiple orthopoxvirus species and other studies. Both vaccines have solid safety records. MVA-BN's replication incompetence favors adoption, whereas LC16m8 has more pediatric data. Additional real-world evidence, in additional geographic settings and special populations (e.g. pregnancy, immune suppression, atopic dermatitis), is needed.